2008
DOI: 10.1103/physrevlett.100.237203
|View full text |Cite
|
Sign up to set email alerts
|

Noncollinear Surface Spin Density by Surface Reconstruction in the Alloy NiMn

Abstract: At the (001) surface of the alloy Ni(50)Mn(50), a noncollinear spin density is observed in real space by spin-polarized scanning tunneling microscopy. The spin density of individual atoms also varies in both size and direction as a function of bias voltage, indicating a noncollinearity in the energy domain. The noncollinearity is driven by a surface reconstruction which breaks the otherwise high surface symmetry. First-principles electronic-structure calculations support the experimental observations and evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…Not only the sign of the asymmetry is preserved, but also the monotonous variation as a function of θ Co . The physical concept reported here can be of general application in a large variety of magnetic substrates with noncollinear ground states: 2 AL Fe/Cu(111) [26], 2 AL Mn/W(110) [22], 1 AL Mn/W(100) [27], 1 AL Mn/Ag(111) [21], 2 AL Fe/W(110) [28], 1 AL Fe/Ir(111) [29], and NiMn(001) [30]. This work opens a way to study not only the coupling of adatoms to those substrates, but also the possible magnetic interactions among atoms in artificial structures built by atomic manipulation.…”
Section: (D) and 2(e) Provided That P T = 0 And Aφ/w < 90mentioning
confidence: 99%
“…Not only the sign of the asymmetry is preserved, but also the monotonous variation as a function of θ Co . The physical concept reported here can be of general application in a large variety of magnetic substrates with noncollinear ground states: 2 AL Fe/Cu(111) [26], 2 AL Mn/W(110) [22], 1 AL Mn/W(100) [27], 1 AL Mn/Ag(111) [21], 2 AL Fe/W(110) [28], 1 AL Fe/Ir(111) [29], and NiMn(001) [30]. This work opens a way to study not only the coupling of adatoms to those substrates, but also the possible magnetic interactions among atoms in artificial structures built by atomic manipulation.…”
Section: (D) and 2(e) Provided That P T = 0 And Aφ/w < 90mentioning
confidence: 99%
“…To reveal the local magnetic ordering, it is necessary to study Fe films with a method sensitive to atomic-scale magnetic structures. Spin-polarized scanning tunneling microscopy (SP-STM) is a suitable technique for studying complex magnetic structures, e.g, those showing zero magnetization (such as antiferromagnetic and non-collinear complex structures) with atomic resolution [3,[10][11][12]. We studied the structural and magnetic properties of Fe films grown on Rh (001) surfaces with low electron energy diffraction (LEED), scanning tunneling microscopy (STM), spin-polarized STM (SP-STM), and MOKE measurements.…”
Section: Introductionmentioning
confidence: 99%
“…A noncollinear spin density was observed by spin-polarized scanning tunneling microscopy on equiatomic NiMn films grown layer by layer on Cu͑001͒. 31 This finding deviates significantly from the expected collinear alignment and was interpreted by a surface reconstruction.…”
Section: Introductionmentioning
confidence: 91%
“…[17][18][19][20] In the last decade, several studies on NiMn were performed in the regime of thin and ultrathin films. [21][22][23][24][25][26][27][28][29][30][31] In an x-ray magnetic circular dichroism study of c͑2 ϫ 2͒ NiMn/ Ni͑001͒ an FM instead of an AFM order was observed and attributed to the lattice distortion. 23,24 An FM order has also been observed for Ni x Mn 100−x films on Cu͑001͒ with a Ni content x Ն 80.…”
Section: Introductionmentioning
confidence: 99%